A concise pathophysiological model of acute appendicitis against the background of the COVID-19 pandemic - Reismann, Marc (Frontiers in Pediatrics, 2022)
One of the most common clinical pictures has become the focus of attention during the COVID-19 pandemic: acute appendicitis with the associated diagnostics and therapy. The aim of the work is to show inconsistencies with regard to epidemiology, pathophysiology and therapy against the background of the pandemic with special attention to the conditions for children and to explain the pathophysiological processes that are likely to underlie the disease based on scientifically plausible models.